Clinal variation in autosomal satellite DNA clusters across a contact zone in Barker Frogs - Souza, Lucas Henrique Bonfim; Ferro, Juan Martín; Gatto, Kaleb Pretto; de Sá, Fábio Perin; Haddad, Célio Fernando Baptista [UNESP]; Lourenço, Luciana Bolsoni (Oxford University Press (OUP), 2025)
Contact zones between genetically divergent lineages offer a unique opportunity to explore gene flow and speciation dynamics. Because satellite DNAs (satDNAs) have high evolutionary rates, they may be useful for comparing related taxa and assessing contact zones. Here, we analysed the distribution of chromosomal clusters of PcP190 satDNA across a contact zone between two distinct genetic lineages of a Neotropical species complex of frogs. The parental lineages, Physalaemus ephippifer and lineage 1B (L1B), exhibited pronounced divergence in the number of PcP190 clusters. We further expanded the geographic scope of this species complex by including two additional Brazilian localities in previously available cytogenetic and mitochondrial DNA datasets. The contact zone exhibited remarkable variation in the chromosomal distribution of PcP190 clusters among the autosomes; the only fixed autosomal site was found on chromosome 3. The highest numbers of PcP190 clusters were observed in specimens collected at sites near (approximately 320 km from) the distribution of L1B, whereas specimens from Dom Eliseu, which is near (approximately 330 km from) the distribution of P. ephippifer, had the lowest numbers of such clusters. Mitochondrial haplotypes also exhibited geographical variation across sites. Our findings expand the known contact zone of these Physalaemus lineages from 1,500 km2 to over 6,200 km2, demonstrating its extensive area, and emphasize the usefulness of satDNAs in studying contact zones.
Keywords: centromeric heterochromatin; chromosome polymorphism; PcP190 satDNA; Physalaemus cuvieri—Physalaemus ephippifer species complex